Desain Pembelajaran Terjemah melalui Instagram dengan Pendekatan Skill - Rahmawati, Suci (Aphorisme: Journal of Arabic Language, Literature, and Education, 2022)
This study aims to describe the skilled approach in dance lessens through Instagram. Instagram is one of the social media that can be used as a learning tool because it is easily accessible by anyone, anywhere, and anytime. that the research data is obtained, as explained in the content analysis. In this study, it can be seen how the Skill approach in dance lessens through Instagram. Where the Skill approach is an approach that emphasizes students being able to master and apply Arabic in everyday life. Tarjamah learning it self aims so that anyone who learns a foreign language can use, understand and understand other people.